Preservative of Coconut Sap Shelf Life derived from Mangosteen Yellow Latex - Erista Adisetya; Andreas Wahyu Krisdiarto (JITIPARI, 2022)
The quality of coconut sap (nira) is a significant aspect of the manufacturing of palm sugar. Coconut nira deteriorates fast, and handling nira in the field is challenging due to the long duration of the tapping process, and coconut trees are high, making it tough to reach. The use of natural preservatives to nira help in the preservation of its quality prior to processing. The objectives of this study are to 1) develop a natural coconut nira preservatives formula from mangosteen yellow latex and 2) evaluate the dose of preservatives necessary to maximize nira's shelf life. The study employed a randomized complete analysis with four preservative concentrations of 0%, 1%, 1.5%, and 2%. and four different storage durations: zero hours, six hours, twelve hours, and twenty-four hours. Chemical analysis of pH, total acid, total sugar, and reduced sugar was performed, as well as sensory evaluation. The study concluded that yellow mangosteen latex can help in the preservation of coconut nira. Preservative concentrations of 1.5% and 2% are still acceptable in 12 hours of storage. While a concentration of 1% is allowed for storage of up to 6 hours. If no preservatives are applied, nira should be processed shortly after harvesting. Nira's quality is deplorable after 24 hours of storage.